Evaluation of a branding model with emphasis on organizational social responsibility based on social networks in the banking industry and the structural equation method - Isa Fahim; Mojtaba Poursalimi; Ali Hosseinzadeh; Mohammad Ghasemi Namaghi (Cogent Business & Management, 2021)
The purpose of this study is to evaluate a branding model with an emphasis on organizational social responsibility based on social networks in the banking industry. The statistical population of the study includes all the employees of Sepah Bank in Iran. The 384 people were selected as the sample of the study using the Cochran formula. Qualitative content analysis and structural equation analysis using PLS software were used for data analysis. The results showed that the dimension of factors had a positive and significant relationship with the dimension of processes and results. The results also showed that the process dimension has a positive and significant relationship with the dimension of the results. Also, the results of the further analysis showed that among the three main dimensions of the model (factors, processes, and results), the process dimension had the most impact on the results dimension, indicating that Sepah Bank must pay more attention to its business processes to increase its social responsibility.
Keywords: 650; social responsibility; social networks; banking industry